1999
DOI: 10.1074/jbc.274.44.31131
|View full text |Cite
|
Sign up to set email alerts
|

A New 30-kDa Ubiquitin-related SUMO-1 Hydrolase from Bovine Brain

Abstract: SUMO-1 is a ubiquitin-like protein functioning as an important reversible protein modifier. To date there is no report on a SUMO-1 hydrolase/isopeptidase catalyzing the release of SUMO-1 from its precursor or SUMO-1-ligated proteins in mammalian tissues. Here we found multiple activities that cleave the SUMO-1 moiety from two model substrates, 125 I-SUMO-1-␣NH-HSTVG-SMHISPPEPESEEEEEHYC and/or GST-SUMO-1-35 SRanGAP1 conjugate, in bovine brain extracts. Of them, a major SUMO-1 C-terminal hydrolase had been parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 19 publications
(19 reference statements)
1
65
1
Order By: Relevance
“…Since then, numerous additional enzymes have been isolated from yeasts and mammalian cells. (Li and Hochstrasser, 2000;Suzuki et al, 1999;Gong et al, 2000b;Nishida et al, 2000;Kim et al, 2000;Schwienhorst et al, 2000). These have been variously called SENPs (for`Sentrin-speci®c protease'; Gong et al, 2000b;Yeh et al, 2000), SUSPs (SUMOspeci®c protease; Kim et al, 2000) or SMT3IP1 (Nishida et al, 2000).…”
Section: Ulp (Senps/susps)mentioning
confidence: 99%
“…Since then, numerous additional enzymes have been isolated from yeasts and mammalian cells. (Li and Hochstrasser, 2000;Suzuki et al, 1999;Gong et al, 2000b;Nishida et al, 2000;Kim et al, 2000;Schwienhorst et al, 2000). These have been variously called SENPs (for`Sentrin-speci®c protease'; Gong et al, 2000b;Yeh et al, 2000), SUSPs (SUMOspeci®c protease; Kim et al, 2000) or SMT3IP1 (Nishida et al, 2000).…”
Section: Ulp (Senps/susps)mentioning
confidence: 99%
“…5 Different members of these SUMO-specific proteases appear to localize in different cellular compartments where they regulate protein function by modifying the protein stability, cellular localization, and protein-protein interactions. 5,6,[8][9][10][11][12] However, it is not known how these SUMO-specific proteases are regulated.HIPK1 is one of three closely related serine/threonine protein kinases that are primarily localized in the nucleus where it is sumoylated. 13,14 The HIPKs were originally identified as nuclear protein kinases that function as co-repressors for various homeodomain-containing transcription factors.…”
mentioning
confidence: 99%
“…4 Several members of SUMOspecific proteases have been reported in the mammalian system. [5][6][7][8][9][10] SENP1 is a protease that appears to deconjugate a large number of sumoylated proteins. 5 Different members of these SUMO-specific proteases appear to localize in different cellular compartments where they regulate protein function by modifying the protein stability, cellular localization, and protein-protein interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction is probably due to lower-affinity ionic interactions and made the purification of the sumoylated fraction of the LANA2 protein difficult. Taken together, these results demonstrated that LANA2 is sumoylated by SUMO1 and SUMO2 in vitro and by SUMO2 in vivo.To confirm that endogenous LANA2 protein is sumoylated in KSHV-infected cells, protein extracts from BC-1 cells prepared in the presence of N-ethylmaleimide, which has been previously shown to stabilize SUMO-modified proteins (Suzuki et al, 1999), were immunoprecipitated with anti-LANA2 antibody. Western-blot analysis of the immunoprecipitates using anti-LANA2 antibody revealed a major band of approximately 75 kDa, corresponding to LANA2, and two additional slower-migrating bands: one broad band of about 95-100 kDa that might correspond to the band detected in the in vitro sumoylation assay after incubation with SUMO1 and a light band of about 120 kDa (Fig.…”
mentioning
confidence: 99%